Correlation between changes in paleoceanography, paleoclimate and methane seepage on Vestnesa Ridge, eastern Fram Strait. - Myrvang, Karoline (UiT Norges arktiske universitet, 2015)
Two sediment cores HH14-002 GC and HH12-930 GC from Vestnesa Ridge in the eastern part of Fram Strain have been investigated to reconstruct the paleoclimate and paleoceanographic conditions during the last ~37,000 years, and to study possibly changes in emission of methane from the seabed through time. Core HH14-002 GC was taken from outside a pockmark, while core HH12-930 GC was taken from inside the pockmark. The two sediment cores HH14-002 GC and HH12-930 GC were divided into six lithological units based on the differences in magnetic susceptibility, lithology, concentration of IRD, grain size distribution and results from stable isotope analysis. HH14-002 GC show a similarity in magnetic susceptibility and lithology to the sediment cores in the study by Jessen et al. (2010), while HH12-930 GC show mainly similarity in lithology. An age model could be established by correlating the results from HH14-002 GC and HH12-930 GC with Jessen et al (2010). The age of the cores ranges from 37,829 to 14,070 cal. yr BP, and covers intervals from the mid-Weichselian to early Holocene. Deposition of mass transported sediments in HH14-002 GC and HH12-930 GC indicates that the Svalbard-Barents Sea Ice Sheet reached the shelf break at ~23,820 cal. yr BP, and is a sign of a fully glaciated shelf. After the deglaciation (~20,101 cal. yr BP) and the Heinrich event 1 (~17,652 cal. yr BP) fine-grained laminated sediments were deposited between 14,780 and 14,300 cal. yr BP by turbid meltwater plume. Due to increased bottom currents, parts of the Holocene is missing from HH14-002 GC. Based on the foraminiferal assemblage distribution, concentration of IRD, stable isotope analysis and the age model the paleoceanographic conditions could be reconstructed. The results indicate influence of Atlantic intermediate water during the upper stage of the mid-Weichselian, and during the LGM, where the productivity was high with presence of seasonal sea-ice in the area. During Heinrich event 1 the water column was stratified and the productivity ...